Literature review on the integration of ecosystem services in agricultural economic models - Rojas Lara, T.; Regimi, A.; Kleinwechter, U. (Bioversity International, 2015)
Most analytic tools used in assessing gains from investments in agricultural research either fail to take into consideration environmental impacts or, if they do, it is at a very limited level. The CGIAR Research Programs adopt a systems approach and require a fully integrated consideration of biodiversity and ecosystems services (ESS). This document therefore reviews existing methodologies and available data to identify how biodiversity and ESS can be integrated into analyses at multiple scales; households, farms, landscapes, agriculture sector and economy-wide. The literature review is also designed to identify possible synergies between models at different scales to enable a better understanding of trade-offs between agricultural systems, their environment and human well-being.